Properties of eggshell-derived hydroxyapatite coatings on titanium produced by micro-arc oxidation method / Tawfik Hamood Qaid - Tawfik Hamood , Qaid (2019)
Hydroxyapatite (HA) composite coating can enhance the biocompatibility properties of Titanium (Ti) and its alloys significantly. Hence, developing HA from natural resources and forming bio-ceramic composite coating on Ti and its alloys is highly essential in its application as bone-like implants. In the present study, eggshell-derived hydroxyapatite (EHA) containing coatings were successfully produced on Ti6Al4V substrates using micro-arc oxidation process (MAO) at various concentrations of EHA in an electrolyte consisting of solitary tri-sodium orthophosphate. The effects of different EHA concentrations and passivation on the attributes of the coated specimens were analyzed utilizing X-ray diffraction (XRD), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), Field emission scanning electron microscopy (FESEM), and Energy dispersive X-ray spectroscopy (EDX), respectively. The adhesion strength was evaluated using micro scratch tester, while the corrosion behavior of the produced MAO specimens in phosphate buffer solution (PBS) was determined by an electrochemical method. The consistently controlled experimental studies demonstrated that increasing the EHA concentration to the base electrolyte has resulted in increased thickness, roughness and enhanced crystallinity, whereas, the porosity of the coating layers decreased due to the higher amount of calcium (Ca) and phosphate (P) incorporated into the pores. Rendering to the EDS results, Ca, P, Mg were detected on the surface of MAO coatings and the amount of these elements increased with increasing the EHA content. High concentration of EHA has resulted in an inferior adhesion strength, while the corrosion resistance of the produced MAO coatings was found to be enhanced significantly compared to bare Ti6Al4V substrate.